Pariwisata Berkelanjutan Sebagai Upaya Penguatan Destinasi Wisata Pasca Pandemi di Desa Ekowisata Pancoh Sleman Yogyakarta - Sri Puspa Dewi, Roels Ni Made; Natalia, Dessy; Lorenza, Felicia Augustine (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2023)
The purpose of this study is to identify ecotourism activities that lead to the concept of sustainable tourism. Furthermore, from this description, one can examine the sustainability of tourism from three aspects, namely environmental, economic, and socio-cultural. The research method used is qualitative research with an exploratory approach. Data collection methods through observation, interviews, and documentation. Retrieval of informants with purposive sampling which took as many as 20 people as sources. The data that has been collected is analyzed with an interactive model. The results of this study are that the Pancoh Ecotourism Village has implemented the principles of sustainable tourism starting from participation, carrying capacity and promotion. The implementation of sustainable tourism from the socio-cultural aspect is in the form of incorporating elements of local culture into tourist attractions such as the Wiwitan tradition and learning gamelan. Environmental aspects by utilizing sustainable resources such as recycling waste, using cow dung to become biogas, and making crafts from local bamboo materials. The economic aspect is increasing people's welfare through empowering homestays. The benefits obtained from these three aspects have made Pancoh Ecotourism Village maintain its existence and strengthen destinations through tourism activities based on conservation and utilizing existing resources. Keywords: Sustainable Tourism,Destination Strengthening, Post Pandemic, Ecotourism